De antikoloniale etnografie en postkoloniale inschikkelijkheid in de Zuid-Afrikaanse reisverslagen van Antoni Rehman - Zajas, Paweł (Department of Dutch and South African Studies, Faculty of English, 2008)
The paper is devoted to the ethnographic work of Antoni Rehman (1840-1917) – the first attempt, in Polish, at a scientific description of the southern part of the African continent. In the course of the analysis it becomes evident that the ethnographic writings of Antoni Rehman are involved in the intricate relations of colonialism in a way not apparent at first glance. In his evaluation of indigenous peoples, Rehman first and foremost emphasizes the aspirations of certain groups (particularly the ‘Kaffirs,’ as the Xhosas and Zulus were referred to at that time) to self-sufficiency and independence from Boer and English domination. The South African indigenous peoples thus become a metaphor for Polish post-partition history. Rehman demonstrates his anti-colonial views likewise on a broader level, through his repeated contempt and condemnation of the colonization of nations and ethnic groups, such as the English and Afrikaner policies towards the black majority, as well as British attempts at seizing the Boer Republics (Rehman’s first stay in South Africa coincided with the annexation of Transvaal in 1877). Still, on a more detailed level, for instance in Rehmans’s description of European minorities, positive evaluation is bound up not with anti-colonial attitudes, but rather with successful colonization and the accumulation of goods. In this case, the German people are placed on top of the civilization ladder, while the Boers are depicted as if they were by their nature defined as a people who do not have the right to their own modern state. The Polish researcher has internalized the Prussian ideology of progress which relegates less organized nations to the margins of history. Accordingly we see to which extent postcolonial nostalgia and consciously hailing from the colonized part of Europe determine the nature of Polish-South African ethnography.
Keywords: ethnographic literature; postcolonial theory; travel writing; South Africa